Incorporation of either molybdenum or tungsten into formate dehydrogenase from Desulfovibrio alaskensis NCIMB 13491; EPR assignment of the proximal iron-sulfur cluster to the pterin cofactor in formate dehydrogenases from sulfate-reducing bacteria - Brondino, Carlos D. (2013)
J Biol Inorg Chem (2004) 9: 145–151 DOI 10.1007/s00775-003-0506-z